В поисках новых идентичностей: Украина в этнорегиональном измерении - Прибыткова, И. (Социология: теория, методы, маркетинг, 2001)
The main task of the presented article is to introduce the results of new indentities construction in version of inhabitants of Ukraine. The civil, ethnic, social, language, property and financial self-identification of representatives of different ethnicregional groups of population are investigated. Their foreign policy orientations and home politics priorities, differences between the appraisals of various social groups participation in the new independent state building up are analysed. The levels of political activities and participation in social life, notions of the inhabitants of different regions about their rights of free choice of own way of development and progress are examined in the article. Great attention is given to discussion of Russian language status in Ukraine.